"I have more support around me to be able to change": a qualitative exploration of probationers' and parolees' experiences living in sober living houses. Issue 1 (7th May 2019) - DeGuzman, Rebecca; Korcha, Rachael; Polcin, Douglas
Abstract : Purpose: Persons in the USA who are incarcerated for drug offenses are increasingly being released into the community as a way to decrease prison and jail overcrowding. One challenge is finding housing that supports compliance with probation and parole requirements, which often includes abstinence from drugs and alcohol. Sober living houses (SLHs) are alcohol- and drug-free living environments that are increasingly being used as housing options for probationers and parolees. Although a few studies have reported favorable outcomes for residents of SLHs, little is known about resident experiences or the factors that are experienced as helpful or counterproductive. The paper aims to discuss this issue. Design/methodology/approach: This study conducted qualitative interviews with 28 SLH residents on probation or parole to understand their experiences living in the houses, aspects of the houses that facilitated recovery, ways residence in an SLH affected compliance with probation and parole, and ways the houses addressed HIV risk, a widespread problem among this population. Interviews were audiotaped and coded for dominant themes. Findings: Study participants identified housing as a critically important need after incarceration. For residents nearing the end of their stay in the SLHs, there was significant concern about where they might live after they left. Residents emphasized that shared experiences and goals, consistent enforcement of rules (especially the requirement of abstinence) and encouragement from probation and parole officers as particularly helpful. There was very little focus in HIV issues, even though risk behaviors were fairly common. For some residents, inconsistent enforcement of house rules was experienced as highly problematic. Research is needed to identify the organizational and operational procedures that enhance factors experienced as helpful. Research limitations/implications: Data for this study are self-reported views and experiences. Therefore, the study may not tap into a variety of reasons for resident experiences. In addition, the data set was small ( n =28) and limited to one city in the USA (Los Angeles), so generalization of results might be limited. However, SLHs represent an important housing option for criminal justice involved persons and knowledge about resident experiences can help guide organization and operation of houses and identify areas for further research. Originality/value: This paper is the first to document the views and experiences of persons on probation or parole who reside in sober living recovery houses. These data can be used by SLH operators to develop houses that are responsive to factors experienced as helpful and counterproductive. The significance of this paper is evident in the trend toward decreasing incarceration in the USA of persons convicted of drug offenses and the need for alcohol- and drug-free alternative living environments.